2018
DOI: 10.3389/fphar.2018.01104
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Anti-glioblastoma Chemotherapy Affects Proteoglycan Composition of Brain Extracellular Matrix in Rat Experimental Model in vivo

Abstract: Temozolomide (TMZ) is a conventional chemotherapy drug for adjuvant treatment of glioblastoma multiforme (GBM), often accompanied by dexamethasone (DXM) to prevent brain oedema and alleviate clinical side effects. Here, we aimed to investigate an ability of the drugs to affect normal brain tissue in terms of proteoglycan (PG) composition/content in experimental rat model in vivo. Age- and brain zone-specific transcriptional patterns of PGs were demonstrated for 8, 60, and 120 days old rats, and syndecan-1, gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 44 publications
2
22
0
4
Order By: Relevance
“…We have shown for the first time that the long-term administration of TMZ to elderly Wistar rats leads to an increase in the total content of GAGs and the redistribution of sulfated GAGs between chondrocytes and the matrix of the epiphyseal cartilage of the knee joints. It is interesting that similar changes in GAGs content were observed in the rat brain tissue, where TMZ increases the CS content (one of the main classes of GAGs) in the cerebral cortex of rats after 5 days of drug administration [37].…”
Section: Discussionsupporting
confidence: 56%
“…We have shown for the first time that the long-term administration of TMZ to elderly Wistar rats leads to an increase in the total content of GAGs and the redistribution of sulfated GAGs between chondrocytes and the matrix of the epiphyseal cartilage of the knee joints. It is interesting that similar changes in GAGs content were observed in the rat brain tissue, where TMZ increases the CS content (one of the main classes of GAGs) in the cerebral cortex of rats after 5 days of drug administration [37].…”
Section: Discussionsupporting
confidence: 56%
“…144 TMZ treatment also alters proteoglycan and GAG composition, with the combination of TMZ and dexamethasone resulting in deterioration of proteoglycan and GAG content. 145 Other agents promote TME remodelling that slows tumour progression. Microtubule inhibitors target cell division, but they can also reduce the invasive capacity of tumour cells by reducing MMP-2 expression.…”
Section: Microenvironmental Changesmentioning
confidence: 99%
“…Tsidulko's work demonstrated that PG composition and ECM structure in normal brain tissue were affected during temozolomide induced chemotherapy. These changes were believed to participate in the development of the tumorigenic niche for the expansion of the residual glioma cells and the disease progression (59). Recently, researchers have reviewed the influences of KS sulfation on electrosensory tissues and neuronal regulation.…”
Section: Keratan Sulfate (Ks)mentioning
confidence: 99%